Remini. The Jacksonian Era - Torok, George (Teaching History: A Journal of Methods, 1991)
This book is a fine summary of Remini’s extensive work on the Jacksonian period. Well-written and easily read, it may serve as either an introduction or quick review of the era. It is a volume in the American History Series, which editor John Hope Franklin describes as works where major historians write "not only where the subject stands in today’s historiography but also about where they stand on their subject." Remini succeeds in doing both.